An analytical model for supplier selection. (2017) - Kumar, Darshan; ,
Supplier selection acts as the pivotal role in an enterprise's business development, with future competitive ability in an industrial environment. The selecting process mainly involves evaluation of different alternative suppliers based on different criteria. Both qualitative and quantitative factors have to be considered and a trade-off is made between tangible and intangible factors while selecting a supplier. In the present paper, an analytical model has been developed for selecting supplier for Indian chemical organisations using TOPSIS method. In the present example, we have attempted to give empirical evidence to provide manufacturing managers a practical methodology for selecting suitable suppliers. It has been concluded that quality products are beneficial only if their customers are satisfied with the service being provided by the suppliers.